PELAKSANAAN PENILAIAN DAN IMPLIKASINYA DALAM PEMBENTUKAN SIKAP ILMIAH DAN MOTIVASI BELAJAR MAHASISWA - Sukino Sukino (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2015)
This article would like to description result of research was done entitled the effect of application an examination for student’s science attitude and learning motivation in State Islamic Religious Institutes Pontianak. The problem in this research is first, how to effect of regularly test, and how to effect of take home test, and which do from third tests above very influences for student’s science attitude and learning motivation. This research was done based student’s attitude phenomena in learning activities especially to learn in faced an examination of semester in the Campus. That it was can looked from student’s activities very busy and so-so, tending to be lazy person. Based on pre investigation was discovered the information that student’s character not very busy to learn because lecturer always given test by taken home. But at the same time was discovered the information that student very occupied in quest the hand book, make a summary, and to borrow the notation of matters to another student to prepare to follow end an examination of semester regularly. This research characterized an associative by quantitative approach. That sampling of research was about 100 students taken by random sampling. Meanwhile, Method to aggregate the date used indirect communication technique by questionnaire instrument. Furthermore, to analysis the date used non parametric descriptive statistic. It was done crosstab test by using SPSS 18.0 version that the outcome this research pointed that the implementation of regularly test more influence for student’s science attitude and learning motivation.